A prospective assessment of costs and benefits of renewable energy use in the European union. Issue 1 (February 2016) - Resch, Gustav; Welisch, Marijke; Liebmann, Lukas; Breitschopf, Barbara; Held, Anne
This article presents the outcomes of an assessment of expected costs and benefits of future renewable energy use in the European Union by 2020 and beyond. A binding European Union-wide renewable energy systems target of achieving at least 27% renewable energy systems share in gross final energy demand by 2030 was adopted by the Council of the European Union in October 2014. This has to be seen as an important first step in defining the framework for renewable energy systems post-2020. Other steps, like a clear concept for and an agreement on the effort sharing across Member States have to follow. For doing so, clarity on associated costs and benefits of the future renewable energy systems expansion across European Union Member States appears highly beneficial. The aim of this article is to contribute to the renewable energy systems policy debate, providing an indication of costs and benefits resulting from increased renewable energy systems deployment within the European Union in the 2020 and 2030 frameworks. Within the discussion of costs and benefits, we follow a standardized concept that takes into account the diversity of policies in force and depicts the cost and benefits of renewable energy systems deployment at different levels, avoiding double counting or mixing up of effects. The outcomes of the analysis presented here remain, however, incomplete, focussing on certain indicators and on a related cross-country comparison rather than presenting a complete overview on expected impacts of future renewable energy systems deployment within the European Union.